Mindfulness Awareness Is Associated With a Lower Risk of Anxiety and Depressive Symptoms in Older Adults With Neurocognitive Disorders - Lam, Linda Chiu Wa; Lee, Allen T. C.; Cheng, Sheung Tak; Yip, Benjamin H. K.; Chan, Wai Chi; Fung, Ada W. T.; Ma, Suk Ling; Cheng, Calvin P. W.; Kong, Ryan; Chiu, Henry T. S.; Lai, Frank H. Y.; Wong, Samuel Yeung Shan (Frontiers in Psychiatry, 2021)
Background: Apart from depressive disorders, there are great interests in adopting mindfulness based interventions (MBIs) for other mental health conditions. Depression and anxiety are common in people with neurocognitive disorders (NCD). The potential of MBIs as an adjuvant treatment in this cognitively at-risk group should be further explored. Objectives: The current study explored the association between depression and anxiety symptoms with dispositional mindfulness in older adults, and if same association stays in the context of cognitive impairment. Methods: The Hong Kong Mental Morbidity Survey for Older People (MMSOP) is an ongoing epidemiology study of the prevalence of neurocognitive and mental disorders in adults aged 60 years or over in Hong Kong. MMSOP evaluated cognitive function, psychiatric symptoms (Clinical Interview Schedule-revised, CIS-R), chronic physical disease burden, psychosocial support, and resilience factors, including dispositional mindfulness as measured by the Mindful Attention Awareness Scale (MAAS). We analyzed the impact of MAAS on CIS-R and potential moderation effects of mindfulness. Results: In March 2021, 1,218 community dwelling participants completed assessments. The mean age of the sample is 69.0 (SD 6.9) years. Eight hundred and two participants (65.7%) were not demented (CDR 0) and 391 (32%) and 25 (2%) were categorized as having mild NCD (CDR 0.5) and major NCD (CDR 1 or more), respectively. One hundred forty-three (11.7%) satisfied ICD-10 criteria for anxiety or depressive disorder as measured by CIS-R. Linear regression analysis showed that female gender, CIRS, and MAAS scores were significant factors associated with CIS-R scores. MAAS scores moderated and attenuated the impact CIRS on CIS-R (adjusted R2 = 0.447, p < 0.001). MAAS scores remained as significant moderator for CIRS in patients with NCD (CDR ≥ 0.5) (adjusted R2 = 0.33, p < 0.001). Conclusion: Interim findings of the MMSOP suggested that dispositional mindfulness is associated with lower level of mood symptoms in community dwelling older adults in Hong Kong. The interaction effects further suggested that high mindful awareness may reduce the adverse effects of chronic physical morbidity on mental health. The observation stayed in the participants with cognitive impairment. We should further explore MBIs as a non-pharmacological treatment for in older adults at-risk of physical morbidity and cognitive decline.